Museum Balaputra Dewa Sebagai Destinasi Wisata Yang Menawarkan Nilai Historis Dan Edukatif - nurria, shifa; Syariffudin, Syariffudin; Pamulaan, Alif Bahtiar (FLORESIENSIS, 2024)
Located in Palembang City, South Sumatra, Balaputra Dewa Museum one of the top museums in the area, Balaputra Dewa Museum offers visitors from all walks of life an engaging educational experience in addition to its rich historical significance. This study aims to examine how museum contributes to both attracting tourists and increasing understanding local history. Interviews with museum managers, visitor surveys, and examination of relevant data comprise the qualitative research methodology. To determine the essential components that make this museum a hub for tourism and education, collected data was analyzed. The findings demonstrate that Balaputra Dewa Museum's extensive artifact collection and cutting-edge educational initiatives draw visitors. Visitors value opportunity engage with locals and gain firsthand knowledge of their history and culture. The study comes to the conclusion that museum plays a significant role in promoting tourism and education in the Palembang region addition to being a storehouse for historical artifacts.